Analisis Kemandirian Terhadap Depresi Lansia Dengan Riwayat Diabetes Mellitus Di Keluarga Di Kabupaten Pekalongan - Fijianto, Dwi; Rejeki, Herni; Prasojo, Sigit; Faradisi, Firman; Isyti'aroh; Pratiwi, Yuni Sandra (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: The Process of getting old in the elderly certainly experiences many problems both physical and mentally, socio-economically, and biologically. One of the mental and emotional problems that is often found in the elderly is depression. Factors that increase the risk of depression in the elderly include genetic susceptibility, chronic disease and disability, pain, and frustration with limitations in carrying out daily activities. Independence in the elderly can also influenced by the presence of diabetes mellitus (DM) which effects the elderly in the family. This study aims to analyze the independence of elderly people who suffer from diabetes mellitus on the incidence of depression in the Pekalongan Regency.Methods: The research method that will be used is descriptive with a cross-sectional design. Place of research in the Region of Pekalongan Regency. The sampling technique used purposive sampling. Analysis using the Spearman Rho test.Results: The results showed that the value of p = 0.04 if Î± = 0.05 then p <Î± and H1 are accepted, which means there is a relationship between the level of depression and independence in Activity of Daily Living (ADL) in elderly with diabetes mellitus in Pekalongan Regency. Nurses continue to strive to increase independence and control depression in the elderly with DM so that the quality of life of the elderly becomes more optimal.Conclusion: The conclusion of the study is a significant correlation between the Â level of depression and independence in Activity of Daily Living (ADL) in elderly with diabetes mellitus.